MAKNA MEROKOK DIKALANGAN PELAJAR SMA NEGERI 11 PADANG - Ramadhani, Syamrizal - (Pendidikan Sosiologi, 2014)
This thesis examines the meaning of Smoking among Students of SMA 11 and who is the first time they smoked in groups, and smoking is done not only within the school environment, but outside the school they also smoked smoking behavior that occurs in school is not in one generation but the whole involved students from grade one to grade three. Consequently have an impact on schools and students involved from the smoking thing. Smoking is also conducted on students in the school toilet stall and stall and the school also has a strict ban against students who smoke purpose of this study is to describe the cause of the students of SMAN 11 Padang smoking and smoking meaning for students of SMAN 11 Padang.The method used in this research is descriptive qualitative research. The informant study using purposive sampling with informants totaled 15 people. Data was collected in two ways: observation and interviews, while the analysis of the data used is interactive data analysis by Miles and Huberman. through a four-step data collection, data reduction, data display, and conclusion.The results of the research in this thesis it can be concluded that the factors causing the SMA 11 students made up of Padang smoked internal factors: factors derived from the encouragement of self-learners that is the desire of self-learners to try cigarettes, and external factors is a factor that comes from the outside or external impulse self-learners, among other things: (1) the influence of friends, (2) the introduction of the senior school and (3) neighborhood. While the significance of smoking for students of SMAN 11 Padang is (1) to foster a sense of friendship, (2) increase the sense of solidarity and (3) adding the association and friends.